2021
DOI: 10.31729/jnma.6600
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin B12 Deficiency Resembling Acute Leukemia: A Case Report

Abstract: Vitamin B12 deficiency in children can cause megaloblastic anemia, poor growth, and increased chances of infections. It is an important reversible cause of bone marrow suppression which at the time of presentation can mimic hematological malignancy. Therefore, it should be considered as a differential diagnosis in cases suspected of acute leukemia. We report a case of 14 months old child who had atypical presentation of vitamin B12 deficiency. He had chronic fever, decreased feeding and increased paleness for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…Oussalah et al demonstrated in their 2019 systematic review that, in addition to neurological damage, patients who had suffered N2O poisoning had at least one haematological alteration in 71.7% of cases, the 3 main alterations are a drop in haemoglobin level (55.8%), a drop in haematocrit (52.4%) and macrocytosis (41.8%) [ 3 ]. Vitamin B12 deficiency is well recognised as an aetiology of pancytopenia with several cases reported in the literature describing an acute leukaemia-like clinic [ 21 23 ]. To date, only two cases of pancytopenia due to vitamin B12 deficiency induced by recreational use of N2O have been reported [ 24 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Oussalah et al demonstrated in their 2019 systematic review that, in addition to neurological damage, patients who had suffered N2O poisoning had at least one haematological alteration in 71.7% of cases, the 3 main alterations are a drop in haemoglobin level (55.8%), a drop in haematocrit (52.4%) and macrocytosis (41.8%) [ 3 ]. Vitamin B12 deficiency is well recognised as an aetiology of pancytopenia with several cases reported in the literature describing an acute leukaemia-like clinic [ 21 23 ]. To date, only two cases of pancytopenia due to vitamin B12 deficiency induced by recreational use of N2O have been reported [ 24 , 25 ].…”
Section: Discussionmentioning
confidence: 99%